2017
DOI: 10.1016/j.snb.2016.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Integrated platform for detecting pathogenic DNA via magnetic tunneling junction-based biosensors

Abstract: In recent years, the development of portable platforms for performing fast and point-of-care analyses has drawn considerable attention for their wide variety of applications in life science. In this framework, tools combining magnetoresistive biosensors with magnetic markers have been widely studied in order to detect concentrations of specific molecules, demonstrating high sensitivity and ease of integration with conventional electronics. In this work, first, we develop a protocol for efficient hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…The sensor signal first increased as the binding process took place, and a decrease in sensor signal was observed when a washing procedure was conducted. More recent research also demonstrated the detection of different concentrations of DNA extracted from Listeria bacterium with a sensitivity below the nM range [128]. The possibility of multiplexed assay development was also evaluated by examining the orthogonality of the DNA probes.…”
Section: Tmr-based Sensors For Genotypingmentioning
confidence: 99%
“…The sensor signal first increased as the binding process took place, and a decrease in sensor signal was observed when a washing procedure was conducted. More recent research also demonstrated the detection of different concentrations of DNA extracted from Listeria bacterium with a sensitivity below the nM range [128]. The possibility of multiplexed assay development was also evaluated by examining the orthogonality of the DNA probes.…”
Section: Tmr-based Sensors For Genotypingmentioning
confidence: 99%
“…TMR sensors have been used to detect small quantities of iron oxide MPs in the complex lymphatic environment with good spatial resolution [ 175 ]. Additionally, a portable system has been integrated with a microfluidic apparatus as a lab-on-a-chip platform to detect pathogenic DNA below nM range sensitivity [ 176 ].…”
Section: Detection Techniques and Their Applicationsmentioning
confidence: 99%
“…These investigators suggested the utility of this technique in early diagnosis of listeriosis both in clinical and environmental samples. In a recent report, Sharma et al (2017) developed a protocol based on the hybridization of natural DNA, and explored the hybridization events involving genomic DNA extracted from L. monocytogenes through a compact magnetic tunneling junction (MTJ)based biosensing apparatus. In this study, they designed the portable biosensor setup based on MTJ platform to detect L. monocytogenes ( Figure 8A-C).…”
Section: Impedimetric Based Dna Biosensorsmentioning
confidence: 99%